Penerapan Model Pembelajaran Think Pair Share Pada Pelajaran Bahasa Indonesia Untuk Meningkatkan Keterampilan Berbicara Siswa - wulandari, oky (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
activity of choosing, establishing, and developing methods to desired learning outcomes based on existing conditions. During the educational process, students must have good speaking skills. In fact, students have not yet had good speech skills, as evidenced by the lack of communication between teachers and students as well as the student's condition of passivity during learning in the classroom. It attracted researchers to improve the speaking skills of V-grade students by applying the Think Pair Share learning model to the Indonesian language lesson. This study uses qualitative descriptive research taking the population of the entire VC class of 28 students. Data collection with observation and lifting methods. The results of the study showed the effectiveness of speaking skills of VC class students with a percentage of 90,20%. thus can be taken the conclusion that applying the learning model Think Pair Share can improve the speech skills of Class V students